Androgen Receptor Expression and Association With Distant Disease-Free Survival in Triple Negative Breast Cancer: Analysis of 263 Patients Treated With Standard Therapy for Stage I-III Disease - Dieci, Maria Vittoria; Tsvetkova, Vassilena; Griguolo, Gaia; Miglietta, Federica; Mantiero, Mara; Tasca, Giulia; Cumerlato, Enrico; Giorgi, Carlo Alberto; Giarratano, Tommaso; Faggioni, Giovanni; Falci, Cristina; Vernaci, Grazia; et al. (Frontiers in Oncology, 2019)
Background. We evaluated immunohistochemical AR expression and correlation with prognosis in a large series of homogeneously treated patients with primary TNBC. Material and methods. Patients diagnosed with stage I-III TNBC between 2000 and 2015 at Istituto Oncologico Veneto who received treatment with surgery and neoadjuvant and/or adjuvant chemotherapy were included. Whole tissue slides were stained for AR. AR-positive expression was defined as >1% of positively stained tumor cells. Distant-disease-free survival (DDFS) was calculated from diagnosis to distant relapse or death. Late-DDFS was calculated from the landmark of 3 years after diagnosis until distant relapse or death. Results. We included 263 primary TNBC patients. Mean AR expression was 14% (range 0-100%), and 29.7% (n=78) of patients were AR+. AR+ vs AR- cases presented more frequently older age (p<0.001), non-ductal histology (p<0.001), G1-G2 (p=0.003), lower Ki67 (p<0.001) and lower TILs (p=0.008). At a median follow up of 81 months, 23.6% of patients experienced a DDFS event: 33.3% of AR+ and 19.5% of AR- patients (p=0.015). 5-yrs DFS rates were 67.2% and 80.6% for AR+ and AR- patients (HR=1.82 95%CI 1.10-3.02, p=0.020). AR maintained an independent prognostic role beyond stage, but when TILs were added to the model only stage and TILs were independent prognostic factors. AR was the only factor significantly associated with late-DDFS: 16.4% of AR+ and 3.4% of AR- patients experienced a DDFS after the landmark of 3 years after diagnosis (p=0.001). Late-DDFS rates at 5 years from the 3-year landmark were 75.8% for AR+ and 95.2% for AR- patients (log-rank p<0.001; HR=5.67, 95%CI 1.90-16.94, p=0.002). Conclusions: AR expression is associated with worse outcome for patients with TNBC. In particular, AR+ TNBC patients are at increased risk of late DDFS events. These results reinforce the rationale of AR targeting in AR+ TNBC.